Associations between expression of indoleamine 2, 3-dioxygenase enzyme and inflammatory cytokines in patients with first-episode drug-naive Schizophrenia - Yan Zhang (Nature Publishing Group, 2021)
Abstract The indoleamine 2,3-dioxygenase (IDO) enzyme is the first rate-limiting enzyme of the tryptophan degradation pathway in which dysfunction of neuroactive metabolites has been implicated in the pathophysiology of schizophrenia. Inflammatory molecules such as pro-inflammatory cytokines could enhance the activity of IDO. There are few studies on the expression of IDO levels and its correlation with levels of inflammatory cytokines in first-episode drug-naive patients with schizophrenia. One hundred inpatients (female = 33, male = 67) with first-episode drug-naive schizophrenia entered a 6-week, double-blind, randomized, placebo-controlled clinical trial. All individuals were assigned celecoxib or placebo combined with risperidone. Serum levels of IDO and six inflammatory cytokines (IL-1β, IL-6, TNF-α IL-17, IL-4, and INF-γ) were measured. The Positive and Negative Syndrome Scale (PANSS) was used to assess the severity of psychotic symptoms. Compared to healthy subjects, patients had significantly elevated levels of IDO and six cytokines at baseline. Over the 6-week treatment period, the decrease in the levels of IDO and TNF-α and the improvement in the PANSS total score, positive scores, and negative scores in the celecoxib group were significantly greater than in the placebo group. There was a significantly positive correlation between IDO levels and the PANSS negative scores and between IDO levels and TNF-α and IFN-γ levels in the celecoxib group. These findings showed abnormal expression of IDO levels which correlated with negative symptoms and pro-inflammatory cytokine levels in patients with first-episode drug-naive schizophrenia, suggesting the important role of IDO in the pathological mechanism of schizophrenia. Registration number: ChiCTR2000041403.